Gemini/GMOS optical transmission spectroscopy of WASP-121b: signs of variability in an ultra-hot Jupiter?. Issue 4 (22nd March 2021) - Wilson, Jamie; Gibson, Neale P; Lothringer, Joshua D; Sing, David K; Mikal-Evans, Thomas; de Mooij, Ernst J W; Nikolov, Nikolay; Watson, Chris A
ABSTRACT: We present ground-based, spectroscopic observations of two transits of the ultra-hot Jupiter WASP-121b covering the wavelength range ≈500–950 nm using Gemini/GMOS. We use a Gaussian process framework to model instrumental systematics in the light curves, and also demonstrate the use of the more generalized Student's-T process to verify our results. We find that our measured transmission spectrum, whilst showing overall agreement, is slightly discrepant with results obtained using HST /STIS, particularly for wavelengths shortwards of ≈650 nm. In contrast to the STIS results, we find evidence for an increasing bluewards slope and little evidence for absorption from either TiO or VO in our retrieval, in agreement with a number of recent studies performed at high-resolution. We suggest that this might point to some other absorbers, particularly some combination of recently detected atomic metals, in addition to scattering by hazes, being responsible for the excess optical absorption and observed vertical thermal inversion. Our results are also broadly consistent with previous ground-based photometry and 3D GCM predictions, however, these assumed different chemistry to our retrievals. In addition, we show that the GMOS observations are repeatable over short periods (days), similar to the HST /STIS observations. Their difference over longer periods (months) could well be the result of temporal variability in the atmospheric properties (i.e. weather) as predicted by theoretical models of ultra-hot Jupiters; however, more mundane explanations such as instrumental systematics and stellar activity cannot be fully ruled out, and we encourage future observations to explore this possibility.